2009
DOI: 10.1007/s00442-009-1406-x
|View full text |Cite
|
Sign up to set email alerts
|

Physiological responses to nitrogen and sulphur addition and raised temperature in Sphagnum balticum

Abstract: Sphagnum, the main genus which forms boreal peat, is strongly affected by N and S deposition and raised temperature, but the physiological mechanisms behind the responses are largely unknown. We measured maximum photosynthetic rate (NP(max)), maximum efficiency of photosystem II [variable fluorescence (F (v))/maximum fluorescence yield (F (m))] and concentrations of N, C, chlorophyll and carotenoids as responses to N and S addition and increased temperature in Sphagnum balticum (a widespread species in the nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
43
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 57 publications
11
43
1
Order By: Relevance
“…appears to be high compared to a range of Sphagnum N contents for different N deposition sites (Lamers et al, 2000). Optimal growth conditions for Sphagnum balticum were found at an N content of 12.9 mg g −1 (Granath et al, 2009), suggesting that Sphagnum in our experiment is around the saturation point. Indeed, high amounts of inorganic N were still taken up from rainwater by Sphagnum spp., leaving the surface water nearly depleted of N (Table 2).…”
Section: Diazotrophic Activity Under High N Conditionsmentioning
confidence: 61%
“…appears to be high compared to a range of Sphagnum N contents for different N deposition sites (Lamers et al, 2000). Optimal growth conditions for Sphagnum balticum were found at an N content of 12.9 mg g −1 (Granath et al, 2009), suggesting that Sphagnum in our experiment is around the saturation point. Indeed, high amounts of inorganic N were still taken up from rainwater by Sphagnum spp., leaving the surface water nearly depleted of N (Table 2).…”
Section: Diazotrophic Activity Under High N Conditionsmentioning
confidence: 61%
“…These results suggest that mosses may respond with an increased photosynthetic rate to low doses of N addition or deposition (e.g. less than 1 g N/m 2 /year; Granath et al, 2009b). No significant effect of N addition on F v /F m of Sphagnum spp.…”
Section: Introductionmentioning
confidence: 82%
“…Thus, mosses are expected to be sensitive to N addition, especially physiologically (Manning et al, 2006;Granath et al, 2012). Granath et al (2009b) found a unimodal response of photosynthesis with a N concentration optimum for photosynthetic capacity at around 1.3% for Sphagnum balticum. Positive relationships were also observed in a greenhouse experiment (Granath et al, 2012) and along a latitudinal nitrogen deposition gradient (Granath et al, 2009a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Atmospheric N deposition increases N content in Sphagnum mosses (Aerts et al 1992;Bragazza et al 2005;Granath et al 2009;Jiroušek et al 2011). Less is known about rates of atmospheric P deposition, which have a high degree of spatial variation (Tipping et al 2014) and are thus more difficult to assess in terms of their impact on Sphagnum P concentration.…”
Section: Introductionmentioning
confidence: 99%